Complex assessment of inland water fish stocks - Stündl, László (Acta Agraria Debreceniensis, 2007)
In the domestic fish production, natural waters have yielded for several years about 7-8 thousand tons. This, from the point of view of outputs, considering the almost 130 thousand hectares of natural water, is rather low, it means approximately 55-60 kg/ha mixed fish.Although the various natural waters can differ significantly on the basis of yields, yet on the majority of the territories, the results were low. In the case of our extensive still waters and rivers, the reason can undoubtedly be found in the combined effect of the lack of the possibility of reproduction of the fish stock and the over-fishing. Fishery built on planning supposes the best possible knowledge in the given circum stances of the parameters of the water area and its fishstock. Lacking this knowledge, it is not possible to establish the optimal use fulness of the resources, what is more, the management can make faulty decisions – as a result of a lack of information -, which can risk the success of later activities. It is known that many factors have an impact on the success of the fishery, as well as some information in connection with the water area and the fish stock are necessary, the knowledge of which make it possible to manage the fishery in a planned way. One part of the information is available, while the other part is incomplete or not deep enough. The necessary data are dissimilar depending on their nature, can be obtained from different places, by different methods. As the first step for executing the field surveys and processing data, I developed a complex model, which contains in a unified system the steps of estimating the fishstock. I made the sampling on the basis of this. Part of the model is a fish faunistic survey, as well as a morphological survey of the water area. The information gained from these are important for making more accurate the system of devices of the samplings for stock estimation (duration, number of net-rows) and for assigning its place (places representing the best way the physical characteristics of the given water area). The major stages of stock-survey: A) faunistic survey, B) physical survey of the bed, and C) sampling with the help of gill-nets. This is followed by the evaluation by the computer module. The results of the research create a methodological and technical background for the fish faunistic and population biologic surveys still performed in different ways in our country, and by applying these methods together, all basic information about natural waters which help decision-making concerning fisheries can be obtaine deffectively.